PROFIL DARAH (HEMOGLOBIN DAN HEMATOKRIT) BROILER JANTAN YANG DIBERI Nigella sativa (JINTAN HITAM) SEBAGAI IMUNOMODULATOR - Rizki Tikadewi Noviani; Purnama Edy Santosa; Sri Suharyati; Siswanto Siswanto (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
The purpose of this study was to determine the description of the blood profile especially hemoglobin and hematocrit of male broiler chickens that given Nigella sativa (black cumin seed). This research was conducted on 18 December 2019-16 January 2020 at the Integrated Field Laboratory, Faculty of Agriculture, Lampung University and Pramitra Biolab Indonesia Clinical Laboratory, Bandarlampung. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments given in this study were broiler chickens drinking water without Nigella sativa (P0), drinking water with 36 mg/kg BW/day of Nigella sativa (P1), drinking water with 72 mg/kg BW/day of Nigella sativa (P2), drinking water with 144 mg /kg BW/day of Nigella sativa (P3). Data were analyzed descriptively (histogram). The results showed that application of Nigella sativa at a dose of 144mg /kg BW/day (P3) was the optimal dose to increase hemoglobin levels and hematocrit values of male broiler chicken. Keywords: Black cumin, hemoglobin, hematocrit, immunomodulator, male broiler, Nigella sativa